2022
DOI: 10.1021/acschemneuro.2c00402
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Actions of H2S-Releasing Peptides in Human β-Amyloid Expressing C. elegans

Abstract: Alzheimer’s disease (AD) is a debilitating progressive neurodegenerative disorder characterized by the loss of cognitive function. A major challenge in treating this ailment fully is its multifactorial nature, as it is associated with effects like deposition of Aβ plaques, oxidative distress, inflammation of neuronal cells, and low levels of the neurotransmitter acetylcholine (ACh). In the present work, we demonstrate the design, synthesis, and biological activity of peptide conjugates by coupling a H2S-releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…We also reported amyloid-like structures formed by cysteine and methionine and unusual aggregates formed by proline, hydroxyproline, and lysine. , Our studies suggested that the aggregates formed by these nonaromatic amino acids were cytotoxic in nature and reduced cell viability. , Gazit and co-workers also extended the ‘generic amyloid hypothesis’ to assemblies formed by nonproteinaceous metabolites such as uracil, cystine, and orotic acid . Subsequently, the group also reported a yeast model for monitoring the accumulation and fibrillation of adenine. , The same research group also reported the formation of amyloid-like aggregates by other metabolites such as quinolinic acid, oxalate, and glucosylceramide and illustrated their implications in the pathophysiology of associated IEMs. The cytotoxic effects of metabolite assemblies may be mainly attributed to their ability to cause membrane disruption and hemolysis as well as their tendency to cross-seed amyloid characteristics to other proteins. ,,, Hence, motivated by the previous literature and our own interest in biomolecular self-assembly and amyloid research, we attempted to study the aggregation of metabolites of the urea cycle and uric acid pathway in greater detail to understand its association with amyloid-related diseases and assess the implications of this aggregation in the pathogenesis of diseases such as the HHH syndrome, citrullinemia, xanthinuria, Lesch–Nyhan syndrome (LNS), and gout caused by the accumulation and excess of these metabolites.…”
Section: Introductionmentioning
confidence: 67%
“…We also reported amyloid-like structures formed by cysteine and methionine and unusual aggregates formed by proline, hydroxyproline, and lysine. , Our studies suggested that the aggregates formed by these nonaromatic amino acids were cytotoxic in nature and reduced cell viability. , Gazit and co-workers also extended the ‘generic amyloid hypothesis’ to assemblies formed by nonproteinaceous metabolites such as uracil, cystine, and orotic acid . Subsequently, the group also reported a yeast model for monitoring the accumulation and fibrillation of adenine. , The same research group also reported the formation of amyloid-like aggregates by other metabolites such as quinolinic acid, oxalate, and glucosylceramide and illustrated their implications in the pathophysiology of associated IEMs. The cytotoxic effects of metabolite assemblies may be mainly attributed to their ability to cause membrane disruption and hemolysis as well as their tendency to cross-seed amyloid characteristics to other proteins. ,,, Hence, motivated by the previous literature and our own interest in biomolecular self-assembly and amyloid research, we attempted to study the aggregation of metabolites of the urea cycle and uric acid pathway in greater detail to understand its association with amyloid-related diseases and assess the implications of this aggregation in the pathogenesis of diseases such as the HHH syndrome, citrullinemia, xanthinuria, Lesch–Nyhan syndrome (LNS), and gout caused by the accumulation and excess of these metabolites.…”
Section: Introductionmentioning
confidence: 67%
“…Information regarding the inhibition process will further help to develop better medication for other neurodegenerative diseases. 101,[125][126][127][128][129] Fig. 15 Schematic presentation of the formation of nano-aggregates in the presence of metal ions with a higher charge-to-radius ratio resulted in the enhancement of the blue intrinsic fluorescence property.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the inhibition process will further help to develop better medication for other neurodegenerative diseases. 101,125–129…”
Section: Discussionmentioning
confidence: 99%
“…A separate study utilizing NaHS and Tabiano's spa-water (rich in sulfur compounds) ameliorated behavioral deficits in three experimental models of AD [93]. H 2 S donors were also tested in a C. elegans model of AD and shown to reduce Aβ aggregation, increase levels of acetylcholine, and reduce oxidative stress [94]. Another study reported that dietary methionine restriction in APP/PS1 mice ameliorated neurodegeneration, improved cognition, and increased H 2 S production [95].…”
Section: H 2 S and Admentioning
confidence: 99%